Organic Light‐Emitting Diodes: Charge Recombination in Polaron Pairs: A Key Factor for Operational Stability of Blue‐Phosphorescent Light‐Emitting Devices (Adv. Theory Simul. 8/2020). Issue 8 (10th August 2020) - Odinokov, Alexey; Osipov, Alexey; Oh, Juwon; Moon, Yu Kyung; Ihn, Soo‐Ghang; Lee, Hasup; Kim, Inkoo; Son, Won‐Joon; Kim, Sangmo; Kravchuk, Dmitry; Kim, Jong Soo; Kim, Joonghyuk; et al.
Abstract : Interaction of charge carriers inside organic light‐emitting diodes (OLEDs) often results in the formation of highly reactive polaron pairs causing degradation of the emitting layer. In article number 2000028, Dongho Kim, Youngmin You, Alexander Yakubovich, and co‐workers develop a simulation approach to calculate charge recombination rates in materials of different polarity. The ability to predict device lifetime is demonstrated.